Evaluasi Usability User Interface Website Menggunakan Metode Usability Testing Berbasis ISO 9241-11 (Studi Kasus Portal Universitas Alma Ata) - Faiz Anas; Muhammad Asman; Deden Hardan Gutama (Himpunan Penggiat Teknologi Informasi Abrar Indonesia, 2022)
Alma Ata University Portal is a platform intended for Alma Ata University students as an information center in the form of a web, ranging from announcements, class schedules, payment information and so on. The purpose of this research is to test the performance/function of the Alma Ata University portal in meeting student satisfaction as well as in certain services and interests. the sample of this study were students from the University of Alma ata who were still active. The sample was carried out using purposive sampling by distributing questionnaires containing several tasks that needed to be done. The method used in this research is Usability Testing (ISO) 9241-11 with Performance Measurement technique. The results of this study indicate that the performance of the Alma Ata university portal is quite good with an average effectiveness value of 75% where this value belongs to the moderate level or can also be called normal. while in the measurement of the efficient aspect, the average value of the relative efficiency is 77% and is included in the normal category.